Retrieval of extruded mineral trioxide aggregate using a novel suction device - Meenu Dhiman; Jigyasa Duhan; Ruchi Juneja; Sanjay Tewari; Pankaj Sangwan (Wolters Kluwer Medknow Publications, 2018)
Treatment of necrotic immature permanent teeth is an exigently demanding situation for an endodontist. Regenerative endodontic procedures are being employed for such teeth in a hope to restore a functional pulp tissue and continue root development. However, currently advocated techniques may not be effective in retaining mineral trioxide aggregate (MTA) in its coronal position. The present paper describes two immature teeth with pulpal necrosis and apical periodontitis that were treated through revascularization. In both the cases, apical extrusion of the coronal MTA plug occurred. A suction tip was customized to completely retrieve the extruded material. Both cases proved out to be a clinical and radiographic success over extended follow-up periods.